Refractory carcinoid syndrome: a review of treatment options - Rachel P. Riechelmann; Allan A. Pereira; Juliana F. M. Rego; Frederico P. Costa (Therapeutic Advances in Medical Oncology, 2017)
Carcinoid syndrome (CSy) is a constellation of symptoms that may commonly present in patients with well differentiated neuroendocrine tumors (NETs), with somatostatin analogs (SSAs) being the first-line option for symptom management. However, symptomatic progression eventually occurs and in this scenario of a refractory CSy; several treatment options have been studied such as dose escalation of SSA, interferon and liver-directed therapies. Nevertheless, recent phase III trials have contributed to the understanding and management of this condition. We performed a comprehensive review of interventional studies examining refractory CSy to provide the evidence for current treatment options and propose a treatment sequence.